2019
DOI: 10.1007/s00167-019-05431-4
|View full text |Cite
|
Sign up to set email alerts
|

Femoral-tibial fixation affects risk of revision and reoperation after anterior cruciate ligament reconstruction using hamstring autograft

Abstract: PurposeNewer fixation devices for hamstring (HS) autograft have been introduced over the years, yet the impact of these devices on ACLR outcomes requiring surgical intervention remains unclear. We sought to evaluate the risk of aseptic revision and reoperation after HS autograft ACLR according to various femoral‐tibial fixation methods. MethodsA cohort study was conducted using the Kaiser Permanente ACLR Registry. Primary isolated unilateral ACLR patients who received a HS autograft were identified (2007–2014)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…A second issue is related to fixation methods, as a higher revision risk was reported using suspensory fixation, which is typical of the AM portal technique, as opposed to the cross-pin and interference screws usually used in the TT drilling approach. 48 Third, a recent single-surgeon case series of 1480 patients by Clatworthy et al 10 identified a higher risk of failure when the AM portal technique was used compared with the TT approach. However, the different drilling techniques coincided with different graft placement: a “central” footprint position was in fact achieved with the AM portal, while an “eccentric” position within the native footprint, close to the insertion of the ACL direct fibers, was obtained with the TT technique.…”
Section: Discussionmentioning
confidence: 99%
“…A second issue is related to fixation methods, as a higher revision risk was reported using suspensory fixation, which is typical of the AM portal technique, as opposed to the cross-pin and interference screws usually used in the TT drilling approach. 48 Third, a recent single-surgeon case series of 1480 patients by Clatworthy et al 10 identified a higher risk of failure when the AM portal technique was used compared with the TT approach. However, the different drilling techniques coincided with different graft placement: a “central” footprint position was in fact achieved with the AM portal, while an “eccentric” position within the native footprint, close to the insertion of the ACL direct fibers, was obtained with the TT technique.…”
Section: Discussionmentioning
confidence: 99%
“…51 Given this finding, we limited the current study cohort to patients aged 25 years or younger in order to evaluate those patients at the highest risk of revision. Previous studies have also reported a lower revision risk with both crosspin femoral fixation 44 and transtibial drilling. 9,39,47 The allograft ACLR group had higher proportions of these protective factors; however, after adjustment for femoral fixation and tunnel drilling technique in our regression model, we still found a higher risk of revision for the allograft ACLR group.…”
Section: Discussionmentioning
confidence: 78%
“…31 However, the authors did not find an association between the type of tibial fixation and revision risk. In the United States, a study performed by Spragg et al 40 involving 6593 patients recorded in the Kaiser Permanente ACL Registry found a higher reoperation rate with suspensory tibial devices, but no difference in revision risk when compared with interference tibial devices. 40 Surgical practice in New Zealand differs, as nearly all hamstring tendon autografts are fixed with a suspensory device on the femoral side.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, a study performed by Spragg et al 40 involving 6593 patients recorded in the Kaiser Permanente ACL Registry found a higher reoperation rate with suspensory tibial devices, but no difference in revision risk when compared with interference tibial devices. 40 Surgical practice in New Zealand differs, as nearly all hamstring tendon autografts are fixed with a suspensory device on the femoral side. In contrast to these studies, we found a higher revision rate with interference tibial devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation